2021
DOI: 10.1001/jamapsychiatry.2020.4783
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Brief, Peer-Delivered Self-management Intervention for Patients With Rare Chronic Diseases

Abstract: IMPORTANCEPatients coping with rare diseases need psychosocial support.OBJECTIVE To evaluate the efficacy of a brief, transdiagnostic, peer-delivered intervention for patients with rare diseases in addition to care as usual (CAU) compared with CAU only. DESIGN, SETTING, AND PARTICIPANTSIn this 2-group randomized clinical trial conducted from October 5, 2017, to July 12, 2019, patients were recruited via specialized clinics and patient organizations across Germany and participated from home. The study included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 31 publications
0
17
0
2
Order By: Relevance
“…to-peer Ansätze, welche den Austausch mit anderen Betroffenen fördern [13][14][15]. Neue Ansätze in der psychosozialen Unterstützung von Menschen mit chronischen Erkrankungen setzen die Optimierung von krankheitsbezogenen Erwartungen, zum Beispiel in Bezug auf den Verlauf der Erkrankung oder die Wirksamkeit und Verträglichkeit von Behandlungen, in den Fokus.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…to-peer Ansätze, welche den Austausch mit anderen Betroffenen fördern [13][14][15]. Neue Ansätze in der psychosozialen Unterstützung von Menschen mit chronischen Erkrankungen setzen die Optimierung von krankheitsbezogenen Erwartungen, zum Beispiel in Bezug auf den Verlauf der Erkrankung oder die Wirksamkeit und Verträglichkeit von Behandlungen, in den Fokus.…”
Section: Discussionunclassified
“…Darüber hinaus zielen zahlreiche Interventionen darauf ab, die Selbstmanagement-Fähigkeiten von Patient:innen zu verbessern 11 12 . Ebenfalls vielversprechend sind sogenannte Peer-to-peer Ansätze, welche den Austausch mit anderen Betroffenen fördern 13 14 15 . Neue Ansätze in der psychosozialen Unterstützung von Menschen mit chronischen Erkrankungen setzen die Optimierung von krankheitsbezogenen Erwartungen, zum Beispiel in Bezug auf den Verlauf der Erkrankung oder die Wirksamkeit und Verträglichkeit von Behandlungen, in den Fokus.…”
Section: Introductionunclassified
“…Importantly, PLWRD and their advocacy organizations should be included at all stages of the pyramid: they need knowledge and skills for the empowerment, active and meaningful participation in self-care, and advocacy and leadership skills to engage and partner with HWF, researchers, policy makers and regulatory agencies. As PLWRD are experts of their own disease, they could be consulted and engaged into the creation and alignment of educational contents to unmet needs, provision of medical and peer-to-peer education [58][59][60].…”
Section: State-of-the-art In Rare Disease Education: Available Resour...mentioning
confidence: 99%
“…In less prevalent liver diseases, including immune‐related, cholestatic, and genetic CLDs, studies assessing the impact of behavioral health treatment on CLD outcomes are lacking. In primary sclerosing cholangitis, however, it has been shown that improved self‐management through a structured intervention improved HRQOL, coping, and care navigation 21 . In Wilson’s disease, it is known that decoppering does not reduce the burden of psychiatric disease; thus, lifelong management of comorbid psychiatric disorders is likely needed as part of comprehensive care 22 …”
Section: Impact Of Behavioral Health Care On Cld Outcomesmentioning
confidence: 99%
“…In primary sclerosing cholangitis, however, it has been shown that improved self-management through a structured intervention improved HRQOL, coping, and care navigation. 21 In Wilson's disease, it is known that decoppering does not reduce the burden of psychiatric disease; thus, lifelong management of comorbid psychiatric disorders is likely needed as part of comprehensive care.…”
mentioning
confidence: 99%